Electrochemical device

By setting a charging state gradient in the negative electrode composite layer of the lithium ion capacitor and forming a surface structure containing lithium carbonate, the problem of precipitation of metal lithium is solved, and higher reliability and floating charge characteristics are achieved.

CN119856240APending Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380065156.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-08-30
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the negative electrode of the lithium ion capacitor, metal lithium is prone to precipitation, resulting in internal short circuit problems.

Method used

An electrochemical device is designed in which the charging state X% of the end regions in the second direction of the negative electrode composite layer is lower than the charging state Y% of the central region, and the precipitation of metal lithium is suppressed by forming a first layer containing lithium carbonate and a second layer containing solid electrolyte on the surface of the negative electrode composite layer.

Benefits of technology

It effectively suppresses the precipitation of metal lithium on the negative electrode of the electrochemical device, and improves the reliability and floating charge characteristics of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856240A_ABST
    Figure CN119856240A_ABST
Patent Text Reader

Abstract

An electrochemical device includes a positive electrode provided with a positive electrode current collector and a positive electrode mixture layer that is supported on the positive electrode current collector and is reversibly doped with anions, a negative electrode provided with a negative electrode current collector and a negative electrode mixture layer that is supported on the negative electrode current collector and is reversibly doped with lithium ions, a separator, and a lithium ion conductive electrolyte. The length L1 of the negative electrode alloy layer in the first direction is longer than the length L2 of the negative electrode alloy layer in a second direction orthogonal to the first direction, the state of charge of two end regions adjacent to both ends of the negative electrode alloy layer in the second direction is X%, the state of charge of a center region of the negative electrode alloy layer in the second direction is Y%, and Xlt is satisfied; y. This makes it possible to suppress deposition of lithium metal on the negative electrode of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electrochemical devices. Background Art

[0002] In recent years, electrochemical devices that combine the power storage principle of lithium-ion secondary batteries and double-layer capacitors have attracted attention. Such electrochemical devices usually use a polarizable electrode for the positive electrode and a non-polarizable electrode for the negative electrode. As a result, an electrochemical device having both the high energy density of lithium-ion secondary batteries and the high output characteristics of double-layer capacitors is expected (Patent Document 1).

[0003] Patent Document 2 proposes: "A method for producing a negative electrode active material for a lithium ion capacitor, the method comprising: obtaining a negative electrode active material having an average particle size of 12 to 300 nm and a BET specific surface area of ​​200 to 1500 m 2 / g of carbon black is kneaded with a carbon precursor, calcined at 800°C to 3200°C, and pulverized to adjust the average particle size (D50) to 1 to 20 μm and the BET specific surface area to 110 m 2 / g and above and 350m 2 / g below".

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-195231

[0007] Patent Document 2: Japanese Patent No. 6356145 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The negative electrode of an electrochemical device such as a lithium ion capacitor is pre-doped with lithium ions. Therefore, metallic lithium is easily precipitated on the negative electrode. The precipitated metallic lithium may cause an internal short circuit. One of the purposes of the present disclosure is to suppress the precipitation of metallic lithium on the negative electrode.

[0010] Means used to solve problems

[0011] One aspect of the present invention relates to an electrochemical device comprising a positive electrode, a negative electrode, a separator, and a lithium ion conductive electrolyte.

[0012] The positive electrode comprises a positive electrode current collector and a positive electrode composite layer supported on the positive electrode current collector and reversibly doped with anions.

[0013] The negative electrode comprises a negative electrode current collector and a negative electrode composite layer supported on the negative electrode current collector and reversibly doped with lithium ions.

[0014] The length L1 of the negative electrode composite layer in the first direction is longer than the length L2 in the second direction perpendicular to the first direction.

[0015] The charge state of the two end regions adjacent to the two ends of the negative electrode composite layer in the second direction is X%.

[0016] The charge state of the central region of the negative electrode composite layer in the second direction is Y%.

[0017] Satisfy X <Y。

[0018] Effects of the Invention

[0019] According to the present invention, the deposition of metallic lithium on the negative electrode of an electrochemical device can be suppressed.

[0020] The novel features of the present invention are described in the appended claims, but the present invention relates to both the structure and the content, and together with other objects and features of the present application, it should be further fully understood through the following detailed description with reference to the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a longitudinal sectional view showing the structure of an electrochemical device according to one embodiment of the present invention. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. The following description sometimes illustrates specific numerical values ​​and materials, but other numerical values ​​and other materials can be applied as long as the technical solution claimed in the present disclosure can be implemented. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, which can be replaced by "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​of specific physical properties, conditions, etc. are illustrated, as long as the lower limit does not reach above the upper limit, any of the illustrated lower limits can be arbitrarily combined with any of the illustrated upper limits.

[0023] In addition, the present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the appendix. That is, as long as no technical contradiction occurs, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the appendix may be combined.

[0024] In the following description, the term "comprising" or "including" includes expressions such as "containing (or including)", "consisting essentially of", and "consisting of".

[0025] An electrochemical device according to one embodiment of the present invention comprises a positive electrode, a negative electrode, a separator, and a lithium ion conductive electrolyte. Generally, the positive electrode and the negative electrode together with the separator sandwiched therebetween constitute an electrode body. The electrode body is, for example, a columnar winding body formed by winding a strip-shaped positive electrode and a negative electrode with a separator sandwiched therebetween. Alternatively, the electrode body can be formed by stacking a plate-shaped positive electrode and a negative electrode with a separator sandwiched therebetween to form a laminate.

[0026] The positive electrode comprises a positive electrode current collector and a positive electrode composite layer supported on the positive electrode current collector and reversibly doped with anions. The positive electrode composite layer contains at least a positive electrode active material reversibly doped with anions. Doping of anions into the positive electrode composite layer or the positive electrode active material refers to at least the adsorption phenomenon of anions onto the positive electrode active material, and is a concept that may also include chemical interactions between anions and the positive electrode active material. The positive electrode composite layer exhibits capacity by at least performing a non-Faraday reaction of reversibly adsorbing and desorbing anions.

[0027] The negative electrode comprises a negative electrode current collector and a negative electrode composite layer supported on the negative electrode current collector and reversibly doped with lithium ions. The negative electrode composite layer contains at least a negative electrode active material reversibly doped with lithium ions. The doping of lithium ions into the negative electrode composite layer or the negative electrode active material refers to at least a phenomenon of the absorption and storage of lithium ions into the negative electrode active material, and is a concept that may also include the adsorption of lithium ions into the negative electrode active material, the chemical interaction between the negative electrode active material and the lithium ions, etc. The negative electrode composite layer at least performs a Faraday reaction of reversibly absorbing and releasing lithium ions to express the capacity.

[0028] A typical example of the above electrochemical device is a lithium ion capacitor. The positive electrode of a lithium ion capacitor is usually a polarizable electrode. The positive electrode of the polarizable electrode exhibits capacity through the adsorption and desorption of anions on the positive electrode active material. The positive electrode active material, for example, contains carbon materials (activated carbon, etc.). However, the positive electrode can be an electrode that has the properties of a polarizable electrode and at the same time the Faraday reaction also contributes to the positive electrode capacity. Such an electrode, for example, contains a π-conjugated conductive polymer as the positive electrode active material. The conductive polymer may be doped with a dopant. It should be noted that an electrochemical device can also be called a power storage device.

[0029] (negative electrode)

[0030] The negative electrode includes a negative electrode current collector and a negative electrode composite layer. The negative electrode active material reversibly doped with lithium ions includes, for example, hard carbon (non-graphitizable carbon). The thickness of the negative electrode composite layer is not particularly limited, and can be, for example, 10 μm to 300 μm relative to one side of the negative electrode current collector.

[0031] The negative electrode current collector may be a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. As the metal material, copper, a copper alloy, nickel, stainless steel, etc. may be used.

[0032] The interplanar spacing of the (002) plane of non-graphitizable carbon measured by X-ray diffraction (i.e., the interplanar spacing between carbon layers) d002 can be The theoretical capacity of the difficult graphitizable carbon is, for example, ideally 150 mAh / g or more. By using difficult graphitizable carbon, it becomes easy to obtain a negative electrode with a small low-temperature DCR and small swelling and shrinkage associated with charging and discharging. The difficult graphitizable carbon ideally accounts for more than 50% by mass of the negative electrode active material, further more than 80% by mass, and further more than 95% by mass. In addition, the difficult graphitizable carbon ideally accounts for more than 40% by mass of the negative electrode composite layer, further more than 70% by mass, and further more than 90% by mass.

[0033] As the negative electrode active material, the material other than the difficult graphitizing carbon and the difficult graphitizing carbon can be used in combination. As the material other than the difficult graphitizing carbon that can be used as the negative electrode active material, graphitizing carbon (soft carbon), graphite (natural graphite, artificial graphite, etc.), lithium titanium oxide (spinel lithium titanium oxide, etc.), silicon oxide, silicon alloy, tin oxide, tin alloy, etc. can be illustrated.

[0034] The average particle size of the negative electrode active material (particularly non-graphitizable carbon) is preferably 1 μm to 20 μm, more preferably 2 μm to 15 μm, from the viewpoint of high filling property of the negative electrode active material and easy suppression of side reactions with the electrolyte.

[0035] In addition, in this specification, an average particle diameter refers to the volume-based median particle size (D50) in the particle size distribution obtained by the laser diffraction type particle size distribution measurement.

[0036] The shape of the negative electrode is limited by the shape of the negative electrode collector. The shape of the negative electrode collector is usually rectangular, and the shape of the negative electrode composite layer is also usually rectangular. The length L1 of the negative electrode composite layer in the first direction (long side direction) is longer than the length L2 in the second direction (short side direction) orthogonal to the first direction. Rectangles include long strip shapes. The shape of the electrode body constructed in the form of a columnar winding body is usually strip-shaped. The length L1 of the negative electrode composite layer in the first direction can be more than 2 times the length L2 in the second direction, or more than 3 times. When the negative electrode is strip-shaped, an example of a preferred range of L1 / L2 is 8 to 20.

[0037] The negative electrode composite layer has two end regions adjacent to both ends in the second direction. Here, the width of each end region in the second direction is defined as 10% of L2. That is, when the negative electrode composite layer is equally divided into 10 strip regions extending in the first direction from the normal direction of the negative electrode composite layer, the two outermost regions in the second direction are the end regions. 20% of the negative electrode composite layer is the end region.

[0038] The negative electrode composite material layer has a central region including the center in the second direction. Here, the width of the central region in the second direction is defined as 40% of L2. The distances from the center in the second direction of the central region to both ends in the second direction are the same. That is, when the negative electrode composite material layer is equally divided into 10 strip-shaped regions extending in the first direction when viewed from the normal direction of the negative electrode composite material layer, the two most central regions adjacent to the center in the second direction and the two regions adjacent to the most central regions (a total of 4 regions) are the central region.

[0039] Here, if the state of charge (SOC-E) of the end region of the negative electrode composite material layer is X% and the state of charge (SOC-C) of the central region is Y%, the negative electrode composite material layer is formed in such a way that the relationship X < Y is satisfied. SOC-E can be the average of the two end regions. It should be noted that the case where X < Y means that Y is 1.05 times or more of X. In the case where X < Y is satisfied, the precipitation of metallic lithium on the negative electrode can be suppressed.

[0040] The state of charge (SOC) of the negative electrode composite material layer means: when the maximum amount of lithium ions reversibly stored in the negative electrode composite material layer is set to 100%, it is the ratio with respect to the maximum amount of lithium ions reversibly stored in the negative electrode composite material layer.

[0041] The charge termination voltage of the electrochemical device targeted by the present disclosure is, for example, 3.0 V to 4.3 V, and the discharge termination voltage is, for example, 2.0 V to 2.5 V. The rated voltage is, for example, 3.2 V to 4.0 V. Therefore, it is sufficient to satisfy the relationship X < Y when the voltage of the electrochemical device (that is, the potential difference between the positive electrode and the negative electrode) is, for example, 3 V. Generally, the relationship X < Y is always satisfied at a voltage between the charge termination voltage and the discharge termination voltage. It should be noted that an example of the charge termination voltage is 3.8 V, and an example of the discharge termination voltage is 2.2 V. For example, when X < Y is satisfied at 3 V, the precipitation of metallic lithium on the negative electrode can be suppressed.

[0042] However, sometimes it may be insufficient only by designing SOC-E and SOC-C as described above. In order to reduce the internal resistance of the electrochemical device and ensure high reliability (such as high floating charge characteristics), it is desirable that the specific surface area of the negative electrode composite material layer is 10 m 2 / g to 70 m 2 / g.

[0043] The floating charge characteristic is an index of the degree of deterioration of the electrochemical device when performing floating charge to maintain a constant voltage using an external DC power supply. The smaller the capacity reduction during floating charge and the smaller the increase in internal resistance, the better the floating charge characteristic can be said to be.

[0044] When the specific surface area of the negative electrode composite material layer is 10 m 2When the surface area of ​​the negative electrode composite layer is 70 m / g or more, the resistance of the negative electrode is greatly reduced, thereby greatly reducing the internal resistance of the electrochemical device. 2 / g or less, the reactivity of the negative electrode will not increase excessively, and it is easy to suppress the degradation of the negative electrode. Therefore, excellent reliability can be obtained. However, the larger the specific surface area of ​​the negative electrode composite layer, the larger the irreversible capacity, and a large amount of lithium ions need to be pre-doped. On such an electrode, metallic lithium is easily precipitated. The specific surface area of ​​the negative electrode composite layer is further preferably 20m 2 / g~60m 2 / g. In the specific surface area of ​​20m 2 / g or more, metallic lithium is more likely to precipitate.

[0045] In contrast, even when a negative electrode composite layer having a high specific surface area is formed, by designing SOC-E and SOC-C in more detail as described below, it is possible to suppress the precipitation of metallic lithium with a high probability while ensuring high reliability.

[0046] The specific surface area of ​​the negative electrode composite layer is the BET specific surface area calculated using a measuring device in accordance with JIS Z8830 (e.g., TriStar II3020 manufactured by Shimadzu Corporation). Specifically, the electrochemical device is disassembled and the negative electrode is taken out. A half-cell is assembled using the negative electrode as the working electrode and a Li metal foil as the counter electrode, and the Li in the negative electrode is dedoped until the negative electrode potential reaches 1.5V. Next, the negative electrode dedoped with Li is washed with dimethyl carbonate (DMC) and dried. Then, the negative electrode composite layer is peeled off from the negative electrode collector, and a sample of about 0.5g of the negative electrode composite layer is taken.

[0047] Next, the sample was heated at 150°C for 12 hours under reduced pressure of less than 95 kPa, and then nitrogen was adsorbed on the sample of known mass to obtain an adsorption isotherm in the range of relative pressure 0 to 1. Then, the surface area of ​​the sample was calculated based on the monomolecular adsorption amount of the gas obtained from the adsorption isotherm. Here, the specific surface area was calculated using the BET one-point method (relative pressure 0.3) according to the following BET formula.

[0048] P / V(P0-P)=(1 / VmC)+{(C-1) / VmC}(P / P0) (1)

[0049] S=kVm (2)

[0050] P0: saturated vapor pressure

[0051] P: adsorption equilibrium pressure

[0052] V: adsorption amount under adsorption equilibrium pressure P

[0053] Vm: monolayer adsorption capacity

[0054] C: Parameters related to adsorption heat, etc.

[0055] S: Specific surface area

[0056] k: The area occupied by a single nitrogen molecule is 0.162 nm 2

[0057] The difference between X and Y (YX) can be, for example, 5% to 30%, 10% to 30%, or 15% to 25%. By having a difference of 5% or more between X and Y, the precipitation of metallic lithium in the end region can be suppressed with a high probability while ensuring the reliability of the electrochemical device. In addition, by making the difference between X and Y less than 30%, the reliability of the electrochemical device can be improved because a sufficient amount of lithium ions are also pre-doped in the end region.

[0058] When the potential difference between the positive electrode and the negative electrode is 3.0 V, 65%≤X≤85% and 75%≤Y≤95% may be satisfied, 65%≤X≤80% and 80%≤Y≤95% may be satisfied, or 70%≤X≤80% and 85%≤Y≤95% may be satisfied.

[0059] When X is 65% or more or 70% or more, a sufficient amount of lithium ions are pre-doped in the end region. Therefore, it is possible to ensure high reliability of the electrochemical device. In addition, when X is 85% or less or 80% or less, the end region has a sufficient margin for absorbing and storing lithium ions. Therefore, it is possible to suppress the precipitation of metallic lithium in the end region with a high probability.

[0060] When Y is 75% or more, 80% or more, or 85% or more, the internal resistance is reduced and high reliability can be ensured. In addition, when Y is 95% or less, the precipitation of metal lithium can be highly suppressed while ensuring high reliability.

[0061] The SOC of the negative electrode composite layer will change depending on the service life and shelf life of the electrochemical device. Therefore, the above SOC-E and SOC-C values ​​are values ​​measured for the electrochemical device in the initial state as a product. The initial state refers to, for example, a product that has not been completed as a product for a long time, such as within 2 months of completion, and can be in an unused state.

[0062] SOC-E and SOC-C can be measured as follows: a portion is cut from the end area and the central area (preferably the area including the center in the second direction) of the negative electrode composite layer together with the negative electrode collector, and a sample electrode is prepared for measurement. The sample electrode can be, for example, a circular electrode with a diameter of 1 mm to 6 mm (preferably 6 mm). Specifically, a sample battery is prepared having a metal lithium foil as a counter electrode and a sample electrode as a working electrode. A single-layer microporous membrane (for example, a thickness of 16 μm to 25 μm) made of polypropylene (PP) is sandwiched between the metal lithium foil and the sample electrode as a separator. The electrolyte of the sample battery can be an electrolyte of the same composition as the electrochemical device contained in the negative electrode composite layer, and an electrolyte of any composition suitable for charging and discharging the sample battery can be used. Next, the lithium ions contained in the working electrode are discharged until the voltage of the sample battery reaches 1.5 V. Next, the lithium ions are charged from the counter electrode to the working electrode until the voltage of the sample battery reaches the minimum (for example, it reaches less than 1 mV). The current used for charging and discharging is about 0.1 mA / cm 2 (For example, 0.9 mA / cm 2 ~1.1mA / cm 2 ). Based on the charge capacity obtained at this time, SOC-E and SOC-C can be calculated.

[0063] The negative electrode composite layer may contain a conductive aid. As the conductive aid, a carbon material may be used. The conductive aid may be carbon black, carbon fiber, etc. As carbon black, acetylene black (AB), Ketjen black (KB), etc. may be cited. Among them, Ketjen black is ideal in terms of having a large specific surface area.

[0064] In order to increase the specific surface area of ​​the negative electrode composite layer, it is effective to include carbon black as a conductive additive in the negative electrode composite layer. The specific surface area of ​​the negative electrode composite layer can reflect the specific surface areas of the negative electrode active material and the conductive additive. By using a conductive additive with a high specific surface area, the specific surface area of ​​the negative electrode composite layer can be effectively increased, making it easier to reduce the internal resistance of the negative electrode. The specific surface area of ​​the conductive additive is, for example, ideally 800 m 2 / g or more, can also be 1000m 2 Examples of such conductive additives include carbon black (eg, Ketjen Black).

[0065] It should be noted that by observing the cross section of the negative electrode composite layer with a scanning electron microscope (SEM), the volume fraction of the negative electrode composite components including the conductive aid in the negative electrode composite layer can be calculated. Based on the obtained volume fraction and the specific surface area of ​​the negative electrode composite layer, the type and specific surface area of ​​the conductive aid can be inferred. The volume fraction of each negative electrode composite component can be calculated by treating the ratio of the area occupied by each negative electrode composite component in the cross-sectional image as the ratio of the volume. The area ratio can be obtained by analyzing the SEM image with image analysis software.

[0066] The ratio of the mass of the conductive aid to the mass of the negative electrode composite layer is, for example, preferably 2% or more and less than 15%, or 3% or more and 12% or less, or 4% or more and 11% or less. If it is within this range, the resistance of the negative electrode can be suppressed to be sufficiently small, and excellent reliability (especially floating charge characteristics) can be easily ensured.

[0067] The negative electrode composite layer includes a negative electrode active material and a binder that binds the negative electrode active material to the negative electrode collector. The binder includes at least a first component and optionally includes a second component other than the first component. The first component is at least one selected from the group consisting of carboxymethyl cellulose and carboxymethyl cellulose salts (hereinafter, at least one selected from the group consisting of carboxymethyl cellulose and carboxymethyl cellulose salts is also referred to as "CMC".).

[0068] The mass ratio of the first component (CMC) to the mass of the negative electrode composite layer is, for example, 2% or more, 3% or more, or 4% or more. The mass ratio of the first component (CMC) to the mass of the negative electrode composite layer is, for example, 6.0% or less, or 5.0% or less. If it is within this range, the resistance of the negative electrode can be suppressed to be sufficiently small, and the negative electrode composite layer can be bonded to the negative electrode collector with high strength.

[0069] When carboxymethyl cellulose salt is used as CMC, sodium salt, lithium salt, potassium salt, ammonium salt, etc. can be used. Among them, the carboxymethyl cellulose salt preferably contains an ammonium salt. Ammonium salt of carboxymethyl cellulose is particularly unlikely to increase the resistance of the negative electrode among CMCs.

[0070] The mass ratio of the second component to the mass of the negative electrode mixed material layer may be 0% to 3%, 0% to 2%, or 0% to less than 1%. That is, the second component may not be used.

[0071] As the second component, fluororesin, acrylic resin, rubber material, etc. can be listed. As fluororesin, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), modified body of PVDF, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. can be listed. As acrylic resin, polyacrylic acid, acrylic acid-methacrylic acid copolymer, etc. can be listed. As rubber material, styrene-butadiene rubber can be listed.

[0072] The peel strength of the negative electrode composite layer from the negative electrode current collector is preferably ensured to be 0.015 N / mm or more. This peel strength is sufficient from the perspective of manufacturing process and from the perspective of ensuring product characteristics. By increasing the amount of CMC, while ensuring product characteristics, a peel strength of 0.04 N / mm or more, and further 0.05 N / mm or more can be ensured.

[0073] The peel strength of the negative electrode composite layer from the negative electrode collector is determined using a measuring device in accordance with JIS Z0237 (2009). Specifically, the electrochemical device is disassembled and the negative electrode is taken out. The negative electrode is washed with dimethyl carbonate (DMC) and dried. Then, the negative electrode is formed into a strip sample with a width of 10 mm × a length of 50 mm or more. Next, a single side of a double-sided tape (for example, No. 5606 manufactured by Nitto Denko Corporation) with a width of 20 mm × a length of 130 mm is pasted on the negative electrode composite layer of the sample. The other side of the double-sided tape is pasted on a horizontal platform with a flat surface. Then, one end of the length direction of the negative electrode collector is fixed with a dynamometer, and it is stretched in the vertical direction at a speed of 50 mm / minute to peel the negative electrode composite layer pasted on the double-sided tape from the negative electrode collector. The tension at this time is measured for more than 15 seconds, and the average tension in a continuous 15-second interval is calculated.

[0074] The negative electrode material layer is formed by, for example, mixing a negative electrode material with a dispersion medium to prepare a negative electrode slurry, applying the negative electrode slurry to a negative electrode current collector, and then drying the negative electrode material. The negative electrode material includes a negative electrode active material, a binder, a conductive additive, and the like.

[0075] The negative electrode composite layer is pre-doped with lithium ions. By pre-doping the negative electrode composite layer with lithium ions, the potential of the negative electrode is reduced, the potential difference (i.e., voltage) between the positive electrode and the negative electrode is increased, and the energy density of the electrochemical device is improved.

[0076] The negative electrode potential is based on the lithium standard (vs. Li / Li + ) is 0.2 V or less. This negative electrode potential is the negative electrode potential (25° C.) at the end of pre-doping (or during charging). The amount of pre-doped lithium is set in accordance with the negative electrode potential of the electrolyte after the end of pre-doping.

[0077] The surface layer of the negative electrode composite layer may have a first layer containing lithium carbonate. The first layer is mainly formed on the surface of the negative electrode active material. Generally, the larger the specific surface area of ​​the negative electrode composite layer, the easier it is to reduce the floating charge characteristic. By forming the first layer, the deterioration of the negative electrode can be significantly suppressed, and the reduction of the floating charge characteristic can be suppressed.

[0078] The surface layer of the negative electrode composite layer may have a second layer containing a solid electrolyte. At least a portion of the second layer may cover at least a portion of the surface of the negative electrode composite layer via the first layer. The second layer has a composition different from that of the first layer, and the second layer may be distinguished from the first layer. The electrochemical device using lithium ions forms a solid electrolyte interface film (i.e., SEI film) on the negative electrode composite layer during charge and discharge. The second layer may be formed as an SEI film.

[0079] The SEI film plays an important role in the charge and discharge reaction, but if the SEI film is formed too thick, the degradation of the negative electrode will increase. In contrast, the first layer containing lithium carbonate has the function of promoting the formation of a good SEI film and maintaining the SEI film in a good state under repeated charge and discharge. Therefore, by forming the first layer on the surface of the negative electrode composite layer to reduce the resistance of the negative electrode, even if the specific surface area of ​​the negative electrode composite layer is increased, it becomes possible to significantly suppress the degradation of the negative electrode.

[0080] In the case where the negative electrode composite layer has a first layer and a second layer, at least a portion of the second layer covers at least a portion of the surface of the negative electrode active material via the first layer. That is, at least a portion of the first layer is covered by the second layer. The first layer is sandwiched between the surface of the negative electrode active material and the second layer, and constitutes a base layer of the second layer. The first layer constitutes the base layer, and the second layer is formed as a SEI film in a good state.

[0081] The second layer may also contain lithium carbonate. When the second layer contains lithium carbonate, the content of lithium carbonate contained in the second layer is less than the content of lithium carbonate contained in the first layer. By using the first layer containing a large amount of lithium carbonate as the base layer, the second layer is formed as a SEI film in a better state.

[0082] The first layer can be formed on the surface of the negative electrode composite layer before assembling the electrochemical device. The electrochemical device assembled using the negative electrode forms a homogeneous and appropriately thick second layer (SEI film) on the surface of the negative electrode active material through subsequent charging and discharging. The SEI film is formed, for example, by the reaction of the electrolyte with the negative electrode in the electrochemical device. The electrolyte is not only the second layer, but can also pass through the first layer, so the entire surface portion including the first and second layers can be referred to as the SEI film. For convenience in this specification, the second layer is referred to as the SEI film to distinguish it from the first layer.

[0083] The presence of a region containing lithium carbonate such as the first layer can be confirmed by, for example, surface layer analysis using X-ray photoelectron spectroscopy (XPS). However, the analysis method is not limited to XPS.

[0084] The thickness of the first layer may be, for example, 1 nm or more. If a longer-term effect is expected, it may be 5 nm or more. If a more reliable effect is expected, it may be 10 nm or more. However, if the thickness of the first layer exceeds 50 nm, the first layer itself becomes a resistance component. Therefore, the thickness of the first layer may be 50 nm or less, or 30 nm or less. The thickness of the first layer may be, for example, 1 nm to 50 nm.

[0085] The thickness of the second layer may be, for example, 1 nm or more, 3 nm or more, or 5 nm or more. However, if the thickness of the second layer exceeds 20 nm, the second layer itself becomes a resistance component. Therefore, the thickness of the second layer may be set to 20 nm or less, or may be set to 10 nm or less.

[0086] The ratio of the thickness A of the first layer to the thickness B of the second layer, i.e., A / B, is preferably 1 or less from the perspective of reducing the resistance of the negative electrode. In this case, the thickness of the second layer is preferably 20 nm or less, and may be 10 nm or less. However, from the perspective of forming a good second layer, A / B is preferably 0.1 or more, and for example, the A / B ratio may be 0.2 or more.

[0087] The thickness of the first layer and the second layer is measured by analyzing the surface portion of the negative electrode composite layer at multiple locations (at least 5 locations) of the negative electrode composite layer. Then, the average of the thickness of the first layer or the second layer obtained at multiple locations can be used as the thickness of the first layer or the second layer. It should be noted that the negative electrode composite layer used as a measurement sample can be peeled off from the negative electrode collector. In this case, the film formed on the surface of the negative electrode active material near the surface portion of the negative electrode composite layer previously constituted can be analyzed. Specifically, the negative electrode active material covered by the film is taken from the area of ​​the negative electrode composite layer arranged on the side opposite to the side joined to the negative electrode collector for analysis.

[0088] XPS analysis of the surface of the negative electrode composite layer, for example, irradiates the film formed on the surface of the surface or the negative electrode active material in the chamber of an X-ray photoelectron spectrometer with an argon beam, and observes and records the changes of each spectrum belonging to C1s, O1s electrons, etc. relative to the irradiation time. At this time, from the perspective of avoiding analysis errors, the spectrum of the outermost surface of the surface can be ignored. The thickness of the region where the peak belonging to lithium carbonate is stably observed corresponds to the thickness of the first layer.

[0089] In the case of a negative electrode taken out from an electrochemical device that has been completed and aged or charged and discharged at least once, the surface layer of the negative electrode composite layer has an SEI film (i.e., the second layer) containing a solid electrolyte. The thickness of the region where the peaks belonging to the bonds of the compounds contained in the SEI film are stably observed corresponds to the thickness of the SEI film (i.e., the thickness of the second layer).

[0090] As the compound contained in the SEI film, a compound containing an element that can be a marker of the second layer is selected. The element that can be a marker of the second layer refers to, for example, an element (for example, F) that is contained in the electrolyte and is not substantially contained in the first layer. As the compound containing an element that can be a marker of the second layer, for example, LiF can be selected.

[0091] When the second layer contains LiF, a peak of F1s substantially attributable to LiF bonding is observed when the second layer is measured by X-ray photoelectron spectroscopy. In this case, the thickness of the region where the peak attributable to LiF bonding is stably observed corresponds to the thickness of the second layer.

[0092] On the other hand, the first layer generally does not contain LiF, and even when the first layer is measured by X-ray photoelectron spectroscopy, no substantial F1s peak attributable to LiF bonds can be observed. Therefore, the thickness of the first layer can be defined as the thickness of the region where no peak attributable to LiF bonds can be stably observed.

[0093] The SEI film can also be observed to have an O1s peak attributable to lithium carbonate. However, since the SEI film generated in the electrochemical device has a different composition from the pre-formed first layer, the two can be distinguished. For example, the XPS analysis of the SEI film will observe an F1s peak attributable to the LiF bond, while the first layer will not observe a substantial F1s peak attributable to the LiF bond. In addition, the amount of lithium carbonate contained in the SEI film is very small. It should be noted that as a Li1s peak, for example, it is possible to detect a peak derived from, for example, ROCO 2 Peaks of compounds such as Li and ROLi.

[0094] When the first layer is analyzed by XPS, in addition to the first peak of O1s attributed to the C=O bond, a second peak of O1s attributed to the Li-O bond can also be observed. The film region present near the surface of the negative electrode active material may contain a small amount of LiOH or Li 2 O.

[0095] Specifically, when analyzing the first layer of the surface portion constituting the negative electrode composite layer in the depth direction, as the distance from the outermost surface of the surface portion becomes deeper, the first peak (O1s belonging to the C=O bond) and the second peak (O1s belonging to the Li-O bond) are observed, and the first region where the first peak intensity is greater than the second peak intensity, as well as the first peak and the second peak are observed, and the second region where the second peak intensity is greater than the first peak intensity can be observed. In addition, there may be a third region that is closer to the outermost surface of the surface portion than the first region, and the first peak is observed but the second peak is not observed. The third region is easily observed when the thickness of the region containing lithium carbonate is large.

[0096] It should be noted that the magnitude of the peak intensity may be determined based on the height of the peak from the baseline.

[0097] In the center of the first layer in the thickness direction, the C1s peak attributed to the CC bond is generally not substantially observed, and even if observed, the intensity is less than half of the peak intensity attributed to the C═O bond.

[0098] Next, a method for forming the first layer containing lithium carbonate on the surface of the negative electrode mixed material layer will be described. The step of forming the first layer can be performed, for example, by a vapor phase method, a coating method, transfer, or the like.

[0099] As the gas phase method, chemical vapor deposition, physical vapor deposition, sputtering and the like are listed. For example, lithium carbonate can be attached to the surface of the negative electrode composite layer using a vacuum vapor deposition device. The pressure in the chamber of the device during vapor deposition is set to, for example, 10 -2 ~10 -5 Pa, the temperature of the lithium carbonate evaporation source can be 400-600°C, and the temperature of the negative electrode composite layer can be -20-80°C.

[0100] As a coating method, a solution or dispersion containing lithium carbonate is coated on the surface of the negative electrode using, for example, a micro-gravure coater and dried to form the first layer. The lithium carbonate content in the solution or dispersion is, for example, 0.3 to 2% by mass. In the case of using a solution, a concentration below the solubility (for example, about 0.9 to 1.3% by mass if it is an aqueous solution at room temperature) is sufficient.

[0101] Furthermore, a negative electrode can be obtained by performing a step of forming a second layer containing a solid electrolyte in a manner that covers at least a portion of the first layer. The surface layer portion of the obtained negative electrode composite layer has a first layer and a second layer. The second layer is formed in a manner that at least a portion of the second layer covers at least a portion (preferably the entirety) of the surface of the negative electrode active material via the first layer (i.e., the first layer is used as a base layer).

[0102] Since the process of forming the second layer is carried out in a state where the negative electrode composite layer is in contact with the electrolyte, it can also serve as at least a part of the process of pre-doping lithium ions into the negative electrode composite layer. As a lithium ion source for pre-doping, for example, metallic lithium can be used.

[0103] Metallic lithium can be attached to the surface of the negative electrode composite layer. It should be noted that by exposing the negative electrode having the negative electrode composite layer with metallic lithium attached thereto to a carbon dioxide atmosphere, for example, a first layer containing lithium carbonate with a thickness of 1 nm or more and 50 nm or less can be formed.

[0104] The process of attaching metallic lithium to the surface of the negative electrode composite layer can be carried out, for example, by a vapor phase method, transfer printing, etc. As the vapor phase method, methods such as chemical vapor deposition, physical vapor deposition, and sputtering can be cited. For example, metallic lithium can be formed into a film on the surface of the negative electrode composite layer using a vacuum evaporation apparatus. The pressure in the apparatus chamber during evaporation is set to, for example, 10 -2 ~10 - 5 Pa, the temperature of the lithium evaporation source is 400 to 600 °C, and the temperature of the negative electrode composite layer is -20 to 80 °C.

[0105] The negative electrode binder layer satisfying X < Y can be formed, for example, by selectively evaporating metallic lithium in the central region of the negative electrode composite layer. If metallic lithium with a SOC of, for example, 90% or more is evaporated in the central region, lithium ions can be pre-doped into the negative electrode composite layer in such a manner that the SOC gradually decreases from the central region toward the end region. In this case, there is no need to evaporate metallic lithium in the end region. Preferably, when the potential difference between the positive electrode and the negative electrode is 3.0 V, metallic lithium is selectively evaporated in the central region of the negative electrode composite layer in such a manner that the difference between Y and X (Y - X) is 5% or more and 30% or less. Metallic lithium can be evaporated over the entire central region of the negative electrode composite layer, or metallic lithium can be evaporated in a part of the central region. By appropriately selecting the region where metallic lithium is evaporated and the amount of metallic lithium, when the potential difference between the positive electrode and the negative electrode is 3.0 V, a negative electrode satisfying 65% ≤ X ≤ 85% and 75% ≤ Y ≤ 95% can be easily obtained.

[0106] The carbon dioxide atmosphere is preferably a dry atmosphere without moisture, for example, the dew point is -40 °C or lower or -50 °C or lower. The carbon dioxide atmosphere can contain gases other than carbon dioxide. The mole fraction of carbon dioxide is preferably 80% or more, more preferably 95% or more. It is preferably free of oxidizing gases, and the mole fraction of oxygen is set to 0.1% or lower.

[0107] If it is desired to form the first layer thicker, it is efficient to make the partial pressure of carbon dioxide greater than 0.5 atmospheres (5.05×10 4 Pa), and it can also be 1 atmosphere (1.01×105 Pa) or above.

[0108] The temperature of the negative electrode exposed to the carbon dioxide atmosphere may be, for example, in the range of 15° C. to 120° C. The higher the temperature, the thicker the first layer becomes.

[0109] The thickness of the first layer can be easily controlled by changing the time for which the negative electrode is exposed to the carbon dioxide atmosphere. The exposure time may be, for example, 12 hours or longer and less than 10 days.

[0110] The process of forming the first layer is preferably performed before forming the electrode body, but it is not excluded that it is performed after forming the electrode body. That is, a positive electrode is prepared, a negative electrode having a negative electrode composite layer attached with metallic lithium is prepared, a separator is sandwiched between the positive electrode and the negative electrode to form an electrode body, and the electrode body is exposed to a carbon dioxide atmosphere, so that the first layer can be formed on the surface of the negative electrode composite layer.

[0111] It should be noted that the process of pre-doping lithium ions into the negative electrode composite layer is further performed, for example, by subsequently bringing the negative electrode composite layer into contact with an electrolyte, and is terminated by leaving it for a prescribed time. Such a process may be a process of forming the second layer in a manner that covers at least a portion of the first layer. For example, by charging and discharging the electrochemical device at least once, a second layer can be formed in the negative electrode composite layer, and the pre-doping of lithium ions into the negative electrode can be terminated. In addition, for example, by applying a prescribed charging voltage (e.g., 3.4 to 4.0 V) between the terminals of the positive electrode and the negative electrode for a prescribed time (e.g., 1 to 75 hours), the pre-doping of lithium ions into the negative electrode can also be terminated.

[0112] (positive electrode)

[0113] The positive electrode includes a positive electrode active material that is reversibly doped with anions. Examples of the positive electrode active material include carbon materials, conductive polymers, and the like. The positive electrode may include a positive electrode composite layer that includes the positive electrode active material, and a positive electrode current collector that supports the positive electrode composite layer. The thickness of the positive electrode composite layer is not particularly limited, and is, for example, 10 to 300 μm relative to a single side of the positive electrode current collector.

[0114] The positive electrode current collector may be a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. As the metal material, aluminum, an aluminum alloy, nickel, titanium, etc. may be used.

[0115] As the carbon material used as the positive electrode active material, a porous carbon material is preferred, and activated carbon is ideal. As the raw material of the activated carbon, for example, wood, coconut shell, coal, asphalt, phenolic resin, etc. can be cited. The activated carbon is preferably activated.

[0116] The average particle size of the activated carbon is not particularly limited, but is preferably 20 μm or less, and more preferably 3 μm to 15 μm.

[0117] The specific surface area of ​​the positive electrode composite layer roughly reflects the specific surface area of ​​the positive electrode active material. For example, the specific surface area of ​​the positive electrode composite layer is 600 m 2 / g and above 4000m 2 / g or less, the ideal is 800m 2 / g and above 3000m 2 / g or less.

[0118] The specific surface area of ​​the positive electrode composite layer is a BET specific surface area obtained using a measuring device in accordance with JIS Z8830 (e.g., TriStar II3020 manufactured by Shimadzu Corporation). Specifically, the electrochemical device is disassembled and the positive electrode is taken out. Next, the positive electrode is washed with DMC and dried. Then, the positive electrode composite layer is peeled off from the positive electrode collector, and a sample of about 0.5 g of the positive electrode composite layer is taken. Next, the specific surface area of ​​the sample taken is obtained according to the method for measuring the specific surface area of ​​the negative electrode composite layer described above.

[0119] The activated carbon preferably accounts for more than 50 mass %, further more than 80 mass %, further more than 95 mass % of the positive electrode active material. In addition, the activated carbon preferably accounts for more than 40 mass %, further more than 70 mass %, further more than 90 mass % of the positive electrode composite layer.

[0120] The positive electrode composite layer contains a positive electrode active material as an essential component, and contains a conductive agent, a binder, a thickener, etc. as optional components. As the conductive agent, carbon black, carbon fiber, etc. can be listed. As the binder, fluororesin, acrylic resin, rubber material, etc. can be listed. As the thickener, cellulose derivatives, etc. can be listed.

[0121] The positive electrode mixed material layer is formed by, for example, mixing a positive electrode mixed material including a positive electrode active material, a conductive agent, etc., with a dispersion medium to prepare a positive electrode slurry, applying the positive electrode slurry to a positive electrode collector, and then drying the mixture.

[0122] As a conductive polymer that can be used as a positive electrode active material, a π-conjugated polymer is preferred. As a π-conjugated polymer, for example, polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine or their derivatives can be used. These can be used alone or in combination of two or more. The weight average molecular weight of the conductive polymer is, for example, 1000 to 100000. It should be noted that the derivative of the π-conjugated polymer refers to a polymer with a π-conjugated polymer as a basic skeleton, such as polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine, etc. For example, polythiophene derivatives include poly(3,4-ethylenedioxythiophene) (PEDOT) and the like.

[0123] The conductive polymer is formed, for example, by immersing a positive electrode collector having a carbon layer in a reaction solution containing a raw material monomer of the conductive polymer, and electrolytically polymerizing the raw material monomer in the presence of the positive electrode collector. Electrolytic polymerization involves immersing the positive electrode collector and the opposite electrode in a reaction solution containing the raw material monomer, and allowing current to flow between the two using the positive electrode collector as an anode. The conductive polymer can be formed by a method other than electrolytic polymerization. For example, the conductive polymer can be formed by chemical polymerization of the raw material monomer. Chemical polymerization involves polymerizing the raw material monomer using an oxidant or the like in the presence of the positive electrode collector.

[0124] The raw material monomer used in the electrolytic polymerization or chemical polymerization is a polymerizable compound that can generate a conductive polymer by polymerization. The raw material monomer may include an oligomer. As the raw material monomer, for example, aniline, pyrrole, thiophene, furan, thienylethylene, pyridine or their derivatives can be used. These can be used alone or in combination of two or more. Among them, aniline is easy to grow on the surface of the carbon layer by electrolytic polymerization.

[0125] Electrolytic polymerization or chemical polymerization can be carried out using a reaction solution containing anions (dopants). By doping a dopant into a π-electron conjugated polymer, excellent conductivity is exhibited. As dopants, sulfate ions, nitrate ions, phosphate ions, borate ions, benzenesulfonate ions, naphthalenesulfonate ions, toluenesulfonate ions, methanesulfonate ions, perchlorate ions, tetrafluoroborate ions, hexafluorophosphate ions, fluorosulfate ions, etc. can be listed. The dopant can be a polymer ion. As polymer ions, ions of polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, etc. can be listed.

[0126] (Isolated Body)

[0127] The separator is disposed between the positive electrode and the negative electrode. The separator preferably contains, for example, an olefin-based resin. Hereinafter, a separator containing an olefin-based resin is also referred to as an "olefin-based separator."

[0128] Electrochemical devices such as lithium-ion capacitors generally use cellulose-based separators. This is because cellulose-based separators have excellent electrolyte permeability and are easy to pre-dope. On the other hand, since cellulose-based separators have functional groups such as OH groups that easily react with lithium ions and easily contain moisture, they are easily damaged by side reactions. Sometimes the lithium pre-doped into the negative electrode reacts with the separator, and the amount of pre-doped lithium is reduced. In an environment where lithium carbonate is generated on the surface of the negative electrode composite layer, there is a tendency for the cellulose-based separator to deteriorate more rapidly.

[0129] In contrast, the olefin-based separator has a low water content, which can suppress the deterioration of the separator itself and the negative electrode caused by water. The olefin-based separator is also excellent in stability relative to electrolytes containing lithium ions and pre-doped lithium. The olefin-based separator is not easily degraded even in an environment where lithium carbonate is generated on the surface of the negative electrode composite layer. Therefore, by using an olefin-based separator, a low internal resistance state can be maintained for a long time. As a result, the floating charge characteristics of the electrochemical device are improved.

[0130] It should be noted that when lithium ions are pre-doped in a state of a wound body composed of a positive electrode and a negative electrode wound with a separator sandwiched between the positive electrode and the negative electrode, lithium ions dissolved from the metal lithium introduced for pre-doping are difficult to diffuse into the entire wound body. In this case, it is difficult to use an olefin-based separator. On the other hand, by contacting a negative electrode with metal lithium attached to the entire surface of the negative electrode composite layer with an electrolyte for pre-doping, the entire wound body can be pre-doped in a short time.

[0131] Olefin resins are resins containing olefin units as main components. Olefin resins contain, for example, 50% or more by mass, and further 70% or more by mass, of olefin units. Olefin units refer to monomer units derived from olefins (alkenes) such as ethylene, propylene, and butene. Here, the divalent group (diradical) formed by polymerization of the monomer is referred to as the "unit" of the monomer. At least a portion of the olefin may be a derivative thereof. Olefin resins may be homopolymers or copolymers synthesized from a variety of olefins. A portion of the hydrogen atoms of the olefin may be optionally substituted by halogen atoms. Examples of olefin resins may include polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), chlorinated polyethylene (CPE), ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), and the like. Among them, it is preferred to contain at least one selected from the group consisting of polypropylene (PP) and polyethylene (PE). PP is stable relative to an electrolyte containing lithium ions because the separator and the PE separator have high strength, and therefore can be suitably used in an electrochemical device having a first layer and a second layer formed on the surface of the negative electrode composite layer.

[0132] As the separator containing olefin resin, for example, a microporous film, a woven fabric or a nonwoven fabric made of polyolefin can be used. Among them, the microporous film as a non-fibrous porous film has high strength and is suitable for thin film. The thickness of the separator is, for example, 8 to 40 μm, preferably 12 to 30 μm, and more preferably 14 to 25 μm or 16 to 25 μm.

[0133] (Electrolytes)

[0134] The electrolyte having lithium ion conductivity contains a lithium salt and a solvent for dissolving the lithium salt. The anions of the lithium salt can reversibly repeat doping and dedoping of the positive electrode. The lithium ions derived from the lithium salt can reversibly store and release at the negative electrode.

[0135] Examples of lithium salts include LiClO 4 , LiBF 4 、LiPF 6 、LiAlCl 4 、LiSbF 6 、LiSCN、LiCF 3 SO 3 、LiFSO 3 、LiCF 3 CO 2 、LiAsF 6 , LiB 10 Cl 10 、LiCl、LiBr、LiI、LiBCl 4 、LiN(SO 2 F) 2 、LiN(SO 2 CF 3 ) 2 Etc. These may be used alone or in combination of two or more. Among them, lithium salts having fluorine-containing anions are preferred in terms of obtaining a liquid electrolyte with a high degree of dissociation and low viscosity and improving the withstand voltage characteristics of an electrochemical device.

[0136] The electrolyte preferably includes an imide electrolyte. The imide electrolyte includes an imide anion as an anion of the lithium salt. The imide anion may be an anion containing fluorine and sulfur, and lithium bis(fluorosulfonyl)imide, i.e., LiN(SO 2 F) 2 (LiFSI). For example, 80 mass % or more of the lithium salt may be LiFSI.

[0137] It can be considered that LiFSI has the effect of reducing the degradation of the positive electrode active material and the negative electrode active material. It can be considered that among the salts with fluorine-containing anions, FSI anions are not easy to produce by-products due to their excellent stability, which helps to charge and discharge smoothly without damaging the surface of the active material. In addition, the SEI film formed by LiFSI on the surface of the negative electrode composite layer contains a large amount of lithium fluoride, and the content ratio of lithium carbonate is small. Thus, a stable second layer with lithium fluoride as the main component can be formed in a manner that covers the first layer with lithium carbonate as the main component.

[0138] The concentration of the lithium salt in the non-aqueous electrolyte in a charged state (charge rate (SOC) 90 to 100%) is, for example, 0.2 to 5 mol / L.

[0139] As the solvent, cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethylene glycol diethyl ether, trimethoxymethane, sulfolane, methyl sulfolane, 1,3-propane sultone, etc. can be used alone or in combination of two or more.

[0140] The electrolyte may contain various additives as required. For example, unsaturated carbonates such as vinylene carbonate, vinylethylene carbonate, and divinylethylene carbonate may be added as additives to form a lithium ion conductive film on the surface of the negative electrode.

[0141] Figure 1 The structure of an electrochemical device 200 according to one embodiment of the present invention is schematically shown. The electrochemical device 200 includes an electrode body 100, a lithium ion conductive liquid electrolyte (not shown), a metal bottomed battery case 210 that accommodates the electrode body 100 and the electrolyte, and a sealing plate 220 that seals the opening of the battery case 210. The electrode body 100 is formed into a columnar winding body by winding a strip-shaped positive electrode 10 and a strip-shaped negative electrode 20 with a separator 30 sandwiched between the positive electrode 10 and the negative electrode 20. A gasket 221 is arranged on the periphery of the sealing plate 220, and the inside of the battery case 210 is sealed by inserting the open end of the battery case 210 into the gasket 221.

[0142] The positive electrode 10 and the negative electrode 20 each have an exposed portion of the collector at the end along the long side direction, and these exposed portions protrude from different end surfaces of the winding body. The exposed portion 11x of the positive electrode collector is welded to the positive electrode collector plate 13 having a through hole 13h in the center. The other end of the tab lead 15 connected to the positive electrode collector plate 13 at one end is connected to the inner surface of the sealing plate 220. Therefore, the sealing plate 220 has the function of serving as an external positive terminal. On the other hand, the exposed portion 21x of the negative electrode collector is welded to the negative electrode collector plate 23. The negative electrode collector plate 23 is directly welded to a welding member provided on the inner bottom surface of the battery shell 210. Therefore, the battery shell 210 has the function of serving as an external negative terminal.

[0143] The positive electrode collector plate and the negative electrode collector plate are roughly disc-shaped metal plates. The negative electrode collector plate is made of, for example, copper, copper alloy, nickel, stainless steel, etc. The positive electrode collector plate is made of, for example, aluminum, aluminum alloy, titanium, stainless steel, etc.

[0144] Electrochemical devices are not limited to Figure 1 The wound electrochemical device shown in the figure may be a stacked electrochemical device. That is, the electrode body may be a stacked body in which a sheet-like positive electrode and a negative electrode are stacked with a separator sandwiched between the positive and negative electrodes.

[0145] [Example]

[0146] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to the Examples.

[0147] 《Electrochemical devices A1~A7, B1~B9》

[0148] (1) Preparation of positive electrode

[0149] Aluminum foil (positive electrode collector) with a thickness of 30 μm was prepared. On the other hand, 88 parts by mass of activated carbon (average particle size 5.5 μm) as a positive electrode active material, 6 parts by mass of acetylene black (AB) as a conductive agent, 4 parts by mass of carboxymethyl cellulose (CMC) as a thickener, and 2 parts by mass of polytetrafluoroethylene (PTFE) as a binder were dispersed in water to prepare a positive electrode slurry. The obtained positive electrode slurry was applied to both sides of the aluminum foil, the coating was dried, and rolled to form a positive electrode composite layer to obtain a positive electrode. A positive electrode collector exposed portion with a width of 10 mm was formed at the end of the positive electrode collector along the long side direction.

[0150] (2) Preparation of negative electrode

[0151] Prepare a copper foil (negative electrode collector) with a thickness of 10 μm. On the other hand, disperse a total of 95 parts by mass of a negative electrode active material and a conductive aid, as well as 5 parts by mass of an ammonium salt of carboxymethyl cellulose (CMC) as a thickener and styrene-butadiene rubber (SBR) as a binder in water to prepare a negative electrode slurry. Apply the obtained negative electrode slurry on both sides of the copper foil, dry the coating film, and roll it to form a negative electrode composite layer to obtain a negative electrode. As the negative electrode active material, difficult-graphitizable carbon (HC: average particle size 5 μm) is used. As the conductive agent, Ketjen black (KB: specific surface area 800 m 2 By changing the mixing ratio of the negative electrode active material and the conductive additive, the specific surface area of ​​the negative electrode composite layer was adjusted to the values ​​shown in Table 1.

[0152] Then, a thin film of metallic lithium for pre-doping is selectively formed by vacuum evaporation in the central region of the negative electrode composite layer. The amount of pre-doped lithium is set so that the SOS-E and SOC-C obtained by the method described above form the values ​​shown in Table 1 and the negative electrode potential in the electrolyte after the pre-doping is less than 0.2 V relative to metallic lithium.

[0153] Then, a carbon dioxide atmosphere was formed by purging the chamber of the device with carbon dioxide, thereby forming a first layer containing lithium carbonate on the surface of the negative electrode composite layer. The dew point of the carbon dioxide atmosphere was -40°C, the molar fraction of carbon dioxide was 100%, and the pressure in the chamber was set to 1 atmosphere (1.01×10 5 Pa). The temperature of the negative electrode exposed to the carbon dioxide atmosphere at 1 atmosphere was set to 25° C. The time for which the negative electrode was exposed to the carbon dioxide atmosphere was set to 22 hours. The first layer did not substantially contain F (or LiF).

[0154] The peel strength of the negative electrode mixed material layer from the negative electrode current collector was measured and the results were all 0.04 N / mm or more.

[0155] (Electrode Body Fabrication)

[0156] As the separator, a single-layer microporous film (thickness 25 μm) made of polypropylene (PP), which is an olefin-based separator, was used.

[0157] The positive electrode and the negative electrode are wound into a columnar shape with a separator sandwiched therebetween to form an electrode body. At this time, the exposed portion of the positive electrode collector protrudes from one end face of the wound body, and the exposed portion of the negative electrode collector protrudes from the other end face of the electrode body. Disc-shaped positive electrode collector plates and negative electrode collector plates are welded to the exposed portion of the positive electrode collector and the exposed portion of the negative electrode collector, respectively.

[0158] (Preparation of Electrolyte)

[0159] LiFSI as a lithium salt was dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (volume ratio 3:5:2) to prepare a non-aqueous electrolyte. The concentration of LiFSI in the non-aqueous electrolyte was 1.2 mol / L.

[0160] (Assembly of electrochemical device)

[0161] The electrode body is placed in a battery case with an opening and a bottom, and the tab lead connected to the positive electrode collector plate is connected to the inner surface of the sealing plate. Furthermore, the negative electrode collector plate is welded to the inner bottom surface of the battery case. After pouring non-aqueous electrolyte into the battery case, the opening of the battery case is sealed with a sealing plate, and the battery case is assembled as follows. Figure 1In Table 1, A1 to A7 are electrochemical devices of Examples 1 to 5, and B1 to B9 are electrochemical devices of Comparative Examples 1 to 9.

[0162] Then, while applying a charge voltage of 3.8 V between the terminals of the positive electrode and the negative electrode, the battery was aged at 60° C. to complete the pre-doping of the negative electrode with lithium ions.

[0163] The following evaluations were performed on each of the electrochemical devices of Examples and Comparative Examples.

[0164] [Evaluation 1: Measurement of Initial Internal Resistance (DCR) of Electrochemical Device]

[0165] For the electrochemical device just after aging, at -30°C, the positive electrode area is 2 mA / cm 2 After constant current charging at a current density of 2000 volts until the voltage reaches 3.8 V, the voltage of 3.8 V is maintained for 10 minutes. Then, at -30°C, the positive electrode area is charged at 2 mA / cm 2 The battery was discharged at a constant current density until the voltage reached 2.2 V.

[0166] Using the discharge curve obtained by the above discharge (vertical axis: discharge voltage, horizontal axis: discharge time), find the first-order approximate straight line in the range from the start of discharge to 0.5 seconds to 2 seconds, and find the voltage VS of the intercept of the approximate straight line. Determine the value (V0-VS) of the voltage VS minus the voltage V0 at the start of discharge (0 seconds from the start of discharge) as ΔV. Use ΔV (V) and the current value during discharge (current density per unit positive electrode area 2mA / cm 2 × positive electrode area) Id, the internal resistance (DCR) R1 (mΩ) of the electrochemical device was calculated by the following formula (A). This was taken as the initial DCR. The relative values ​​when the initial DCR of the electrochemical device of Comparative Example 2 was set to 100 are shown in Table 1.

[0167] Internal resistance R1=1000×ΔV / Id(A)

[0168] [Evaluation 2: Evaluation of the reliability (floating charge characteristics) of the electrochemical device]

[0169] Next, maintain the state of applying a constant voltage of 3.8 V to the electrochemical device for a long time at an environment of 85°C. At the moment of 1000 hours passing, take out the electrochemical device and discharge it at a current of 5.0 A until 2.5 V. Divide the discharge charge amount flowing during the period from 3.3 V to 3.0 V by the voltage change ΔV (= 0.3 V) to obtain the capacitance C1 (F). For the change rate of the capacitance after continuous charging relative to the capacitance C0 before continuous charging (initial), calculate it through C1 / C0×100. The larger the change rate of the capacitance, the more the rise of the internal resistance is suppressed, the floating charge characteristics are excellent, and the reliability is high. The relative value when setting the initial DCR of the electrochemical device in Comparative Example 3 to 100 is shown in Table 1.

[0170] [Evaluation 3: Evaluation of the precipitation state of metallic lithium]

[0171] Disassemble the electrochemical device that has undergone the reliability evaluation and observe the precipitation state of metallic lithium in the end region of the negative electrode composite material layer. Evaluate the case where metallic lithium is clearly visually confirmed as ×, the case where slight metallic lithium is confirmed as Δ, and the case where no metallic lithium is confirmed at all as 〇.

[0172] Show the evaluation results in Table 1.

[0173] Table 1

[0174]

[0175] No precipitation of metallic lithium was observed in the electrochemical device B1, but the initial DCR was large. That is, if the specific surface area of the negative electrode composite material layer is of a conventional size, even if X < Y is not satisfied, the precipitation of metallic lithium is not likely to pose a problem, but on the other hand, the internal resistance increases.

[0176] The precipitation of metallic lithium in the end region of the negative electrode composite material layer of the electrochemical devices B2 - B7 was significant. It can be considered that this is because although the specific surface area of the negative electrode composite material layer is large, X < Y is not satisfied.

[0177] The reliability of the electrochemical devices B8 - B9 was significantly reduced. It can be considered that this is because the pre-doping amount of lithium ions in the negative electrode composite material layer is insufficient and the internal resistance increases.

[0178] The initial DCR of the electrochemical devices A1 - A5 was low and the reliability was significantly improved. No precipitation of metallic lithium was also observed.

[0179] Only slight precipitation of metallic lithium was observed in the electrochemical device A6.

[0180] No precipitation of metallic lithium was observed in the electrochemical device A7, but the reliability decreased.

[0181] [Evaluation 4: XPS analysis of the surface layer of the negative electrode composite material layer]

[0182] The surface layer of the negative electrode composite layer after exposure to the carbon dioxide atmosphere was analyzed by XPS for C1s spectrum, O1s spectrum, and Li1s spectrum. The analysis was performed using an X-ray photoelectron spectrometer (trade name: Model 5600, manufactured by ULVAC-PHI, Inc.). The measurement conditions are shown below.

[0183] X-ray source: Al-mono (1486.6eV) 14kV / 200W

[0184] Measuring diameter:

[0185] Photoelectron extraction angle: 45°

[0186] Etching conditions: acceleration voltage 3kV, etching rate about 3.1nm / min (SiO 2 Conversion), grating area 3.1mm×3.4mm

[0187] The results of analyzing the C1s spectrum, O1s spectrum, and Li1s spectrum confirmed that the thickness of the first layer was approximately 18 nm. Specifically, peaks of CC bonds, which are presumed to be impurity carbon, were observed on the outermost surface, but decreased sharply near the depth of 1 to 2 nm in the first layer. On the other hand, the first peak belonging to the C=O bond was observed from the outermost surface of the surface part to a depth of 18 nm. Peaks belonging to the Li-O bond were also observed from near the depth of 18 nm. Furthermore, it was successfully confirmed that Li existed stably from the outermost surface of the surface part to a depth of 18 nm. No peak belonging to LiF was observed.

[0188] XPS analysis was performed on the surface of the negative electrode composite layer of the negative electrode taken out from the electrochemical device in the same manner as above, and it was confirmed that a 10 nm thick SEI film (second layer) was formed, which had a composition different from that of the first layer and was distinguished from the first layer. In addition, a peak attributable to LiF was observed.

[0189] (Note)

[0190] Through the above description, the following technology is disclosed.

[0191] (Technology 1)

[0192] An electrochemical device comprising a positive electrode, a negative electrode, a separator, and a lithium ion conductive electrolyte,

[0193] The positive electrode comprises a positive electrode current collector and a positive electrode composite layer supported on the positive electrode current collector and reversibly doped with anions.

[0194] The negative electrode comprises a negative electrode current collector and a negative electrode composite layer supported on the negative electrode current collector and reversibly doped with lithium ions.

[0195] The length L1 of the negative electrode composite layer in the first direction is longer than the length L2 in the second direction perpendicular to the first direction.

[0196] The charge state of the two end regions adjacent to the two ends of the negative electrode composite layer in the second direction is X%.

[0197] The charge state of the central region of the negative electrode composite layer in the second direction is Y%.

[0198] Satisfy X <Y。

[0199] (Technique 2)

[0200] The electrochemical device according to technology 1, wherein the specific surface area of ​​the negative electrode composite layer is 10m 2 / g or more and 70m 2 / g or less.

[0201] (Technique 3)

[0202] The electrochemical device according to technology 1 or 2, wherein the specific surface area of ​​the negative electrode composite layer is 20 m 2 / g or more and 60m 2 / g or less.

[0203] (Technique 4)

[0204] The electrochemical device according to any one of techniques 1 to 3, wherein the negative electrode composite layer contains carbon black as a conductive additive,

[0205] The specific surface area of ​​the conductive additive is 800 m 2 / g or above.

[0206] (Technique 5)

[0207] The electrochemical device according to any one of techniques 1 to 4, wherein a ratio of the mass of the conductive additive to the mass of the negative electrode mixed material layer is 2% or more and less than 15%.

[0208] (Technique 6)

[0209] The electrochemical device according to any one of techniques 1 to 5, wherein when the potential difference between the positive electrode and the negative electrode is 3.0 V, the difference between X and Y (YX) is 5% or more and 30% or less.

[0210] (Technique 7)

[0211] The electrochemical device according to any one of techniques 1 to 6, wherein when the potential difference between the positive electrode and the negative electrode is 3.0 V, 65%≤X≤85% and 75%≤Y≤95% are satisfied.

[0212] (Technology 8)

[0213] The electrochemical device according to any one of techniques 1 to 7, wherein the negative electrode composite layer contains hard carbon as a negative electrode active material.

[0214] (Technique 9)

[0215] The electrochemical device according to any one of Techniques 1 to 8, wherein the positive electrode composite layer contains activated carbon as a positive electrode active material.

[0216] (Technology 10)

[0217] The electrochemical device according to any one of techniques 1 to 9, wherein the surface layer portion of the negative electrode mixed material layer has a first layer containing lithium carbonate.

[0218] (Technology 11)

[0219] The electrochemical device according to any one of techniques 1 to 10, wherein the surface layer of the negative electrode composite layer has a second layer containing a solid electrolyte,

[0220] At least a portion of the second layer covers at least a portion of the surface of the negative electrode mixed material layer via the first layer.

[0221] (Technology 12)

[0222] The electrochemical device according to any one of techniques 1 to 11, wherein the second layer contains lithium carbonate,

[0223] The content of the lithium carbonate contained in the second layer is smaller than the content of the lithium carbonate contained in the first layer.

[0224] (Technology 13)

[0225] The electrochemical device according to any one of Techniques 1 to 12, wherein the separator comprises an olefin-based resin.

[0226] The present invention has been described in terms of the presently preferred embodiments, but this disclosure should not be construed as limiting. Various modifications and changes will undoubtedly become apparent to those skilled in the art of the art to which the present invention pertains by reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes that do not depart from the true spirit and scope of the present invention.

[0227] Industrial Applicability

[0228] The electrochemical device of the present invention is suitable for use in vehicles, for example.

[0229] Explanation of symbols

[0230] 100: Electrode body

[0231] 10: Positive electrode

[0232] 11x: Exposed part of positive electrode current collector

[0233] 13: Positive electrode collector plate

[0234] 15: Tab lead

[0235] 20: Negative electrode

[0236] 21x: Exposed part of negative electrode current collector

[0237] 23: Negative electrode collector plate

[0238] 30: Isolation

[0239] 200: Electrochemical devices

[0240] 210: Battery case

[0241] 220: Sealing plate

[0242] 221: Gasket

Claims

1. An electrochemical device comprising a positive electrode, a negative electrode, a separator, and a lithium ion conductive electrolyte, The positive electrode comprises a positive electrode current collector and a positive electrode composite layer supported on the positive electrode current collector and reversibly doped with anions. The negative electrode comprises a negative electrode current collector and a negative electrode composite layer supported on the negative electrode current collector and reversibly doped with lithium ions. The length L1 of the negative electrode composite layer in the first direction is longer than the length L2 in the second direction perpendicular to the first direction. The charge state of two adjacent end regions of the negative electrode composite layer at both ends in the second direction is X%. The charge state of the central region of the negative electrode composite layer in the second direction is Y%. Satisfy X <Y。 2. The electrochemical device according to claim 1, wherein: The specific surface area of ​​the negative electrode composite layer is 10m 2 / g or more and 70m 2 / g or less.

3. The electrochemical device according to claim 1, wherein The specific surface area of ​​the negative electrode composite layer is 20 m 2 / g or more and 60m 2 / g or less.

4. The electrochemical device according to claim 1, wherein The negative electrode composite layer contains carbon black as a conductive additive. The specific surface area of ​​the conductive additive is 800 m 2 / g or above.

5. The electrochemical device according to claim 4, wherein: The ratio of the mass of the conductive additive to the mass of the negative electrode mixed material layer is 2% or more and less than 15%.

6. The electrochemical device according to claim 1, wherein When the potential difference between the positive electrode and the negative electrode is 3.0 V, the difference between X and Y (YX) is 5% or more and 30% or less.

7. The electrochemical device according to claim 1, wherein: When the potential difference between the positive electrode and the negative electrode is 3.0 V, 65%≤X≤85% and 75%≤Y≤95% are satisfied.

8. The electrochemical device according to claim 1, wherein The negative electrode composite layer contains hard carbon as a negative electrode active material.

9. The electrochemical device according to claim 1, wherein: The positive electrode composite layer contains activated carbon as a positive electrode active material.

10. The electrochemical device according to claim 1, wherein The surface layer of the negative electrode mixed material layer has a first layer containing lithium carbonate.

11. The electrochemical device according to claim 10, wherein: The surface layer of the negative electrode composite layer has a second layer containing a solid electrolyte. At least a portion of the second layer covers at least a portion of the surface of the negative electrode mixed material layer via the first layer.

12. The electrochemical device according to claim 11, wherein The second layer contains lithium carbonate, The content of the lithium carbonate contained in the second layer is less than the content of the lithium carbonate contained in the first layer.

13. The electrochemical device according to any one of claims 1 to 12, wherein: The separator includes an olefin-based resin.

Citation Information

Patent Citations

  • Method for suppressing transverse camber of strip

    JP1988056145B2

  • Nonaqueous lithium power storage device

    JP2017195231A